Hypertension and concomitant diseases: a guide for evidence-based therapy. - Retta, Tamrat M. (National Medical Association, 2004)
Hypertension remains one of the leading causes of morbidity and mortality in the United States. Numerous antihypertensive agents are available today, and most hypertensive patients suffer from concomitant diseases/conditions. Many of these diseases/conditions require appropriate selection of antihypertensive agents. It gets quite complex to pick the initial and additional antihypertensive agents that are simultaneously beneficial in the management of these comorbidities. The authors believe this guide will assist physicians in picking the right agent to achieve goal blood pressure recommended by the Joint National Committee (JNC). In this paper, the introduction section briefly outlines some aspects of the pathophysiology of hypertension. This is followed by subsections that identify commonly encountered diseases/conditions that coexist with hypertension, and a list of antihypertensive drugs to be used for these conditions in the order of preference. The suggested choices are based on evidence from clinical trials, for the most part, and in some cases based on mechanisms of action of the drugs. The list of choices is then followed by concise explanations or rationale, including citations for the clinical trials or other relevant sources. Such a systematic approach and use of a handy flow chart would enhance appropriate blood pressure control and patient compliance and, hopefully, make a little dent in the rate of hypertension-related cardiovascular morbidity and mortality.